(untitled) (Revista de Investigaciones Universidad del Quindío, 2020)
This investigation allowed to carry out a bromatological analysis of the organic solid waste generated in the Aloe Vera processing plant of the Sabimax loe S.A.S company located in the municipality of Montenegro Quindío, which is the product discarded from the agroindustrial processes they perform. Bromatological tests were performed as percentage of humidity, ash, fat, fiber, water activity and pH, and. The analyzes performed on organic solid waste determined that the percentage of humidity is 92.4%. The other physicochemical tests performed on dry matter indicated that 0.43% corresponds to ashes, 39.6% to fiber, 1.25% to ethereal or fat extract and 0.95% is water activity, likewise; a pH of 4.98 was determined. So they were found in an average within the theoretical ranges.